(untitled) (Journal of Bangladesh Institute of Planners, 2015)
The study was conducted to present the development stress on surrounding natural environment associated with rapid urban growth. At the beginning of the study, physical situation of urban expansion of Khulna city is revealed. The urban growth scenario is derived through satellite image analysis of different years on land use land cover (LULC) changes around the city. Image analysis is comprised of supervised classification methods to derive the final results of LULC change. Hereafter, the climatic structure is assessed (changes in Built-up footprint) in relation with changing nature of LULC as well as urban microclimatic conditions. A popular method to detect changing urban microclimatic condition is analysing the changes in the urban microclimatic temperature generally known as Urban Heat Island (UHI) effect. The changing nature of LULC and UHI expresses the emergence of increasing stress of urban areas on the surrounding natural environment. As a result in the study LULC and UHI is assessed to examine the ongoing increasing stress. The result shows the overall increase in the built-up area from the year 1989 to 2014 is about 75.74% (1802.382 acres). The water body cover is reduced up to 153.209 acres and a variation in the fallow land cover is 48.43% in the temporal variation of 25 years. The zonal variation in surface temperature varies 29.64° – 40.71° in the city area and 28.77° – 40.16° outer skirts of the city area with in the time span of 1989 to 2014. Finally, it is seen that the ecological footprint due to built-up footprint is also increasing from the year 1989 to 2014. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 187-194